2020
DOI: 10.1002/cctc.202000400
|View full text |Cite
|
Sign up to set email alerts
|

Second Sphere Ligand Promoted Organoiridium Catalysts for Methanol Dehydrogenation under Mild Conditions

Abstract: Hydrogen produced from renewable resources is a potential source of clean energy. And Methanol is a liquid at room temperature and has a hydrogen content of up to 12.6 wt%, makes it a promising hydrogen source and can provide great benefits for sustainable hydrogen production. In this work, the modification of the picolinic acid ligand along with changes in the type and substituent position of the groups enhances the activity in iridium‐catalyzed methanol dehydrogenation catalysis. These second sphere ligand m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Furthermore, kinetic experiments confirmed the involvement of a hydrogen atom in methanol, with the cleavage of the C-H bond as the rate-determining step. 38 Milstein et al reported the base-free aqueous phase dehydrogenation of methanol (MeOH : H 2 O 4 : 1 v/v) using an acridine-based Ru-PNP catalyst (C-12), where the catalytic activity of C-12 could be enhanced by incorporating one equivalent of a thiol additive. The catalyst C-12 achieved an impressive TOF of 643 h −1 for hydrogen production.…”
Section: Perspectivementioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, kinetic experiments confirmed the involvement of a hydrogen atom in methanol, with the cleavage of the C-H bond as the rate-determining step. 38 Milstein et al reported the base-free aqueous phase dehydrogenation of methanol (MeOH : H 2 O 4 : 1 v/v) using an acridine-based Ru-PNP catalyst (C-12), where the catalytic activity of C-12 could be enhanced by incorporating one equivalent of a thiol additive. The catalyst C-12 achieved an impressive TOF of 643 h −1 for hydrogen production.…”
Section: Perspectivementioning
confidence: 99%
“…Furthermore, kinetic experiments confirmed the involvement of a hydrogen atom in methanol, with the cleavage of the C–H bond as the rate-determining step. 38…”
Section: Hydrogen Production From Methanolmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2013, Nielsen et al published an aqueous-phase reforming of methanol (APRM) method that employed homogeneous Ru-MACHO under 100 °C, resulting in a maximum TOF of 2670 and 350,000 TON for 600 h, without generating CO . Since the publication, there has been investigation into APRM using a homogeneous catalyst. , However, the homogeneous nature of the Ru-MACHO catalyst poses difficulties in separation, resulting in significant challenges for its industrial application. , Due to the advantage of a heterogeneous catalyst in separation, studies have been conducted using various transition metals in APRM with heterogeneous catalysts, but most of them require high temperatures (>200 °C) yet. , Therefore, demonstrating the activity of heterogeneous catalysts under mild conditions (<100 °C) like Ru-MACHO remains a significant challenge in the effective application of fuel cell systems.…”
Section: Introductionmentioning
confidence: 99%
“…16 Recently, Zhou group also demonstrated that the hydroxyl group next to the pyridyl N in pyridine-carboxylate-based iridium catalysts could promote its catalytic activity in methanol dehydrogenation. 17 However, the alkaline reagents such as NaOH or NaOMe used in these catalytic systems prevent acetal formation reaction and further dehydrogenation to form esters. To the contrary, these reactions between alcohol and aldehyde can be catalyzed by Lewis acid that is incompatible with the alkaline condition.…”
mentioning
confidence: 99%